DegS protease regulates the motility, chemotaxis, and colonization of Vibrio cholerae - Zou, Mei; Wang, Kaiying; Zhao, Jiajun; Lu, Huifang; Yang, Hui; Huang, Meirong; Wang, Lu; Wang, Guangli; Huang, Jian; Min, Xun (Frontiers in Microbiology, 2023)
In bacteria, DegS protease functions as an activating factor of the σE envelope stress response system, which ultimately activates the transcription of stress response genes in the cytoplasm. On the basis of high-throughput RNA sequencing, we have previously found that degS knockout inhibits the expression of flagellum synthesis- and chemotaxis-related genes, thereby indicating that DegS may be involved in the regulation of V. cholerae motility. In this study, we examined the relationships between DegS and motility in V. cholerae. Swimming motility and chemotaxis assays revealed that degS or rpoE deletion promotes a substantial reduction in the motility and chemotaxis of V. cholerae, whereas these activities were restored in ΔdegS::degS and ΔdegSΔrseA strains, indicating that DegS is partially dependent on σE to positively regulate V. cholerae activity. Gene-act network analysis revealed that the cAMP–CRP–RpoS signaling pathway, which plays an important role in flagellar synthesis, is significantly inhibited in ΔdegS mutants, whereas in response to the overexpression of cyaA/crp and rpoS in the ΔdegS strain, the motility and chemotaxis of the ΔdegS+cyaA/crp and ΔdegS+rpoS strains were partially restored compared with the ΔdegS strain. We further demonstrated that transcription levels of the flagellar regulatory gene flhF are regulated by DegS via the cAMP–CRP–RpoS signaling pathway. Overexpression of the flhF gene in the ΔdegS strain partially restored motility and chemotaxis. In addition, suckling mouse intestinal colonization experiments indicated that the ΔdegS and ΔrpoE strains were characterized by the poor colonization of mouse intestines, whereas colonization efficacy was restored in the ΔdegSΔrseA, ΔdegS+cyaA/crp, ΔdegS+rpoS, and ΔdegS+flhF strains. Collectively, our findings indicate that DegS regulates the motility and chemotaxis of V. cholerae via the cAMP–CRP–RpoS–FlhF pathway, thereby influencing the colonization of suckling mouse intestines.